The Antecedents of Presenteeism and Sickness Absenteeism: A Research in Turkish Health Sector - Yildiz, Harun; Yildiz, Bora; Zehir, Cemal; Aykac, Mustafa (ELSEVIER SCIENCE BV, 2015)
Presenteeism is usually defined as being in the workplace while sick. On the other hand, sickness absenteeism is absence of employees due to illness. Sickness absenteeism has aroused broad interest in the literature for many years. However, the antecedents of presenteeism are still limited in terms of cultures. In this respect, the aim of this study is to determine the antecedents of presenteeism and sickness absenteeism in Turkish culture. The research examines the effects of working time match and efficiency demands on presenteeism and sickness absenteeism. The data, which consist of 168 Turkish health care employees' responds, was analyzed with logistic regression analysis. As a result of this study, matching of desired and actual weekly working hours decreases presenteeism. We also find that efficiency demands decrease presenteeism for those employees. Lastly, the effects of working time match and efficiency demands on the prevalence of sickness absence and presenteeism are significant. Managerial and further research implications are provided. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Presenteeism; Sickness absenteeism; WORK; ABSENCE; PRODUCTIVITY; ASSOCIATION; ATTENDANCE; WORKPLACE; EMPLOYEES; ILLNESS; Business & Economics